РОД KEYSERLINGITES И ЕГО СТРАТИГРАФИЧЕСКОЕ ЗНАЧЕНИЕ - Ермакова Светлана Петровна; Дагис А.С. (My University, 1986)
The late Olenekian genus Keysrelingites is subdivided into two genera Keyserlingites proper with the type species K. subrobustus and Olenekoceras with the type species K. middendorffi. Diagnoses of the genera and analysis of their stratigraphic range are given.
Keywords: OLENEKOCERAS; LEVIGATUM; 551.761.2(571.56); Мезозой::Триасовая::Нижний::Оленёкский